Aspek Hukum Surat Tanda Nomor Kendaraan Yang Pajaknya Telah Habis Masa Berlaku Saat Dilakukan Pemeriksaan Oleh Polisi Lalu Lintas - Patricia Julia Abrahamsz (Pattimura Legal Journal)
Introduction: The ticket is a fine imposed by the police on road users who violate the regulation. Vehicle registration certificate or STNK for short, is proof of registration and ratification of a motorized vehicle based on its registered identity and ownership. Motor Vehicle Tax is a tax levied on ownership and/or ownership of motorized vehicles.